Study on Material Effort Hypotheses (selected passages from doctoral dissertation) - BURZYNSKI, Włodzimierz (Engineering Transactions, 2009)
Printed in Polish by the Academy of Technical Sciences Lwów, 1928, 1–192. Translated by Teresa Fras and Anna Strek, scientific editor Ryszard B. Pecherski